2022
DOI: 10.3390/buildings12111986
|View full text |Cite
|
Sign up to set email alerts
|

Experimental and Statistical Analysis of U-Shaped Polyurethane-Based Polymer Concrete under Static and Impact Loads as a Repair Material

Abstract: The prolonged service life of civil engineering structures, such as buildings and highway pavement, means that they deteriorate with time, requiring frequent repair work. Polyurethane (PU) materials can effectively maintain engineering structures such as road pavement, runways, and buildings. Thus, the mechanical properties and dynamic performance of these materials for repair are essential to guarantee the safe usage of the facilities. This study investigated the strain–stress behavior and impact strength of … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
5
0

Year Published

2023
2023
2024
2024

Publication Types

Select...
8

Relationship

3
5

Authors

Journals

citations
Cited by 9 publications
(5 citation statements)
references
References 57 publications
0
5
0
Order By: Relevance
“…The impact strength of JFRCs can be assessed by a range of testing procedures, for example, weight loss single or repeat test, weighted pendulum test, projectile test, explosion test, constant strain test, Split-Hopkinson bar test, and instrumented pendulum test. 623–625 The specimen placed between two conical tapered cups was repeatedly hit by a hammer-type pendulum attached to a revolving circular disc. When the release knob set at a fixed angle was touched, it released the pendulum, allowing it to fall.…”
Section: Jfrcsmentioning
confidence: 99%
“…The impact strength of JFRCs can be assessed by a range of testing procedures, for example, weight loss single or repeat test, weighted pendulum test, projectile test, explosion test, constant strain test, Split-Hopkinson bar test, and instrumented pendulum test. 623–625 The specimen placed between two conical tapered cups was repeatedly hit by a hammer-type pendulum attached to a revolving circular disc. When the release knob set at a fixed angle was touched, it released the pendulum, allowing it to fall.…”
Section: Jfrcsmentioning
confidence: 99%
“…At this stage, the overlaid PU grout sustained the applied load to some specific point before the ultimate failure of the NC-PUG composite, indicating the viscoelastic properties of polyurethane, which tend to make concrete more ductile and less brittle. Following the experimental research utilizing polyurethane demonstrates that PU is a very strain rate-sensitive elastomer, with a significant change in performance from rubbery to leathery in response to increased strain rates [42][43][44][45]. Additionally, deflection due to the applied load was recorded at the two end supports, as shown in Figure 7.…”
Section: Flexural Response Of Nc-pugmentioning
confidence: 99%
“…Jongvivatsakul et al [7] reported improved bond strength between carbon-fiber-reinforced polymer plates and concrete using carbon nanotube-reinforced epoxy composites. The U-shaped drop-weight impact testing approach is a newly developed impact testing technique used to evaluate the impact properties of cementitious materials [8][9][10]. The approach evaluated impact strength using a unique U-shaped sample and a repeated drop weight.…”
Section: Introductionmentioning
confidence: 99%